THE DEVELOPMENT OF A STUDENT AFFAIRS MANAGEMENT MODEL FOR SCHOOLS IN THE NEXT DECADE UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE NAKHON SI THAMMARAT - Phetphumiphat, Sorawit; Ekpetch, Chusak; Chairueng, Nopparat (Journal of MCU Nakhondhat, 2026)
This study aimed to: 1) Examine the current conditions and administrative practices of student affairs management in educational institutions; 2) Develop a student affairs management model for educational institutions in the next decade; and 3) Assess the appropriateness and feasibility of the developed model. The study employed a multi-phase mixed-methods research design comprising three phases. Phase 1 focused on investigating the current conditions and administrative approaches to student affairs management. Data were collected from fourteen school administrators. Phase 2 involved developing a future-oriented student affairs management model for the next decade using the Ethnographic Delphi Futures Research (EDFR) technique. The IOC value was determined using five experts.Twenty-one experts with relevant knowledge and professional experience were purposively selected according to predefined criteria. Phase 3 consisted of focus group discussions with nine experts directly involved in student affairs administration in educational institutions. Data collection instruments included semi-structured interview protocols and focus group discussion records. Data were analyzed using content analysis, frequency, percentage, median, and interquartile range. 1) The current direction of student affairs management emphasizes student safety, the integration of technology to support student care, and the application of moral principles and modern administrative processes. Safety has emerged as an urgent policy priority and online threats. While student support systems and moral development are promoted, limitations in teachers’ skills remain. Consequently, schools have increasingly emphasized activities such as art, music, and sports as key tools for student development. 2) The model for student affairs management in educational institutions in the next decade, as derived from the research, is the "SAFED" Model. five key components 3) Evaluation results developed student affairs management model was found to be appropriate and feasible in all aspects. It was found to be appropriate and feasible ( = 4.81, S.D. = 0.53) and beneficial ( = 4.82, S.D. = 0.54).